2016
DOI: 10.1155/2016/2158706
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Performance and Microstructure of Cementitious Materials Made with Dune Sand

Abstract: This paper presents the results of an investigation on the utilization of dune sand from waterway regulation engineering as the main raw materials to produce cementitious materials. The mechanical and durability properties of the cementitious materials were studied. Furthermore, a scanning electron microscope (SEM) and mercury intrusion porosimeter (MIP) were used to identify the microstructure of the specimens. The results show that the compressive and splitting tensile strength of cementitious materials can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The measured compressive strength of all the concrete specimens is shown in Table 6. Test results indicate that the compressive strength decreases with replacement of DS increasing when the replacement level is low, and this trend is consistent with previous literatures (Zhang et al 2006;Al-Harthy et al 2007;Zaitri et al 2014;Belferrag, Kriker, and Khenfer 2013;Abu Seif et al 2016;Alawad et al 2015;Jiang et al 2016;Luo et al 2013). Also, notably, higher replacement of DS aggregates (60%, 80%) causes increasing compressive strength, and this increase is due to absorption of DS which could reduce the water-cement ratio of cement gel.…”
Section: Compressive Strengthsupporting
confidence: 90%
See 2 more Smart Citations
“…The measured compressive strength of all the concrete specimens is shown in Table 6. Test results indicate that the compressive strength decreases with replacement of DS increasing when the replacement level is low, and this trend is consistent with previous literatures (Zhang et al 2006;Al-Harthy et al 2007;Zaitri et al 2014;Belferrag, Kriker, and Khenfer 2013;Abu Seif et al 2016;Alawad et al 2015;Jiang et al 2016;Luo et al 2013). Also, notably, higher replacement of DS aggregates (60%, 80%) causes increasing compressive strength, and this increase is due to absorption of DS which could reduce the water-cement ratio of cement gel.…”
Section: Compressive Strengthsupporting
confidence: 90%
“…Due to the scarcity of aggregates in the areas where aggregate resources are in short supply for environmental reasons, there has been a growing interest in utilization of dune sand (DS) in the production of concrete in structural engineering (Zhang et al 2006;Al-Harthy et al 2007;Bouziani, Bederina, and Hadjoudja 2012;Zaitri et al 2014;Belferrag, Kriker, and Khenfer 2013;Abu Seif et al 2016;Alhozaimy et al 2014;Alawad et al 2015;Jiang et al 2016;Luo et al 2013;Lee, Park, and Kim 2016). The Xinjiang province is located in the northwest of China, and nearly a quarter of Xinjiang is covered with DS due to dry continental climatic conditions (Wang, Xiao, and Li 2007), and the region of Xinjiang is characterized by a lack of fine natural aggregate resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e reason for this phenomenon may be that the excessive gypsum could produce too much ettringite, which results in increased level of internal stress and adversely affects the strength development of the bricks [28].…”
Section: Resultsmentioning
confidence: 99%
“…e results revealed that the desert sand content should not exceed 50% of the total volume of fine aggregate. Rmili et al [12], Bouziani et al [13], Zhang et al [14], Zhang et al [15], Li et al [16], Fu et al [17], Jiang et al [18], and Haifeng et al [19] have also investigated the mechanical properties and influencing factors of desert sand concrete. From the abovementioned literature, it is understood that existing research on desert sand concrete has mainly focused on ordinary concrete, while the application of desert sand to ceramsite lightweight aggregate concrete has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%